Effect of Kinect combination training prescription on postoperative upper limb dysfunction in breast cancer patients: a randomized controlled trial - Zirui, Zhang; Lizhi, Zhou; Yang, Wang; Meijie, Luo; Jiwei, Hu; Aijun, Du; Luyan, Guo; Yijing, Fan; Huiqian, Xu (Supportive care in cancer, 2025)
Purpose To explore the effect of Kinect comprehensive training prescription on upper limb functional rehabilitation of breast cancer patients after surgery. Methods From February 2023 to October 2023, 76 patients with breast cancer who underwent modified radical surgery in the breast surgery department of Tangshan People’s Hospital were included. The patients were randomly assigned to two groups; the control group was given routine nursing, and the experimental group was given routine nursing + comprehensive training prescription of Kinect. Two intervention stages were included, each lasting 7 days. Rewe shoulder function assessment criteria and simplified McGill pain scale scores were collected before intervention, after intervention stages 1 and 2, and at follow-up, and the differences between the two groups were compared. Results (1) Shoulder function: The total Rewe score was higher in the experimental group than that in the control group after intervention ( P < 0.05). (2) Pain: After the first intervention stage, the Pain Assessment Index score was lower in the experimental group than that in the control group ( P < 0.05). There were no significant differences in the total score of the simplified McGill pain scale and scores for all dimensions between the two groups at stage 2 and follow-up ( P > 0.05). Conclusion Kinect comprehensive training prescription can significantly improve the upper limb function and relieve early pain of patients after breast cancer surgery. This method is interesting in operation, novel in form, and has high patient compliance, which lays a foundation for future development and innovative intervention modes.